The Effect of Rambutan Leaves (Nephelium lappaceum Linn) Extract on Tail Bleeding Time in Mice Strain Balb-C - Budi Yuwono; Ratna Indah Cahyani; Sulistiyani Sulistiyani; Dyah Setyorini; Swasthi Prasetyarini (Health Notions, 2023)
Introduction: The most common post-odontectomy bleeding complications were bleeding cases on the first day with a prevalence of 96.6%. Complications of post-odontectomy bleeding if it lasts a long time and is not treated immediately can cause hypovolemic shock, fainting, and further can cause death. Rambutan leaves (Nephelium lappaceum Linn) have several active compounds of tannins, flavonoids, and saponins which have properties to help the hemostatic process by shortening bleeding time. Aims: To examine the effect of rambutan leaves extract (Nephelium lappaceum Linn) on tail bleeding time in balb-C strain mice. Methods: Twelve mice were randomly selected and divided into three groups accordingly; group K- (distilled water), group K+ (tranexamic acid 0.065 mg/g BW), and group P (rambutan leaves extract 260 mg/kg BW). After 60 minutes, the tails of mice were cut along 0.5 cm from the tip of the tail. Bleeding time was observed by turning on the stopwatch along with cutting the tail of the mice and turning it off after the bleeding stopped. Results: Rambutan leaves extract (Nephelium lappaceum Linn) intake at a dose of 260 mg/kg BW had a significant effect (p=0.021) on tail bleeding time, which was to shorten the bleeding time of cutting the tails of mice with Balb-C strain. Conclusions: Based on the results of the study, it can be concluded that rambutan leaves extract (Nephelium lappaceum Linn) has a significant effect on tail bleeding time, which can shorten the bleeding time of cutting the tail of mice with balb-C strain. Keywords: post odontectomy bleeding complications, bleeding time, rambutan leaves extract